2012
DOI: 10.11159/ijtan.2012.003
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the Structure of Electrospun Polyurethane Nanofibrous Materials Used for Bacterial Removal from Wastewater

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Por ejemplo, los valores de eficiencia obtenidos en fibras electrohiladas de nylon-6 son del orden de 99.993%; mientras que, en filtros comerciales, esta eficiencia es de aproximadamente 99.97% (Barhate y Ramakrishna, 2007). Estos sistemas pueden emplearse para gases o líquidos; en el caso de aguas residuales obtenidas en plantas de tratamiento, las nanofibras son funcionalizadas con nanopartículas para reducir la actividad microbiana patógena (Lev, Holba, Kalhotka, Mikula y Kimmer, 2012).…”
Section: Medio Ambienteunclassified
“…Por ejemplo, los valores de eficiencia obtenidos en fibras electrohiladas de nylon-6 son del orden de 99.993%; mientras que, en filtros comerciales, esta eficiencia es de aproximadamente 99.97% (Barhate y Ramakrishna, 2007). Estos sistemas pueden emplearse para gases o líquidos; en el caso de aguas residuales obtenidas en plantas de tratamiento, las nanofibras son funcionalizadas con nanopartículas para reducir la actividad microbiana patógena (Lev, Holba, Kalhotka, Mikula y Kimmer, 2012).…”
Section: Medio Ambienteunclassified
“…The PU-NF base membrane can effectively remove pathogen from waste water upon filtration. Additionally, another work done by Lev, J. et al also showed the fabrication of 0.25 µm PU-NF based membrane, which was able to remove the bacteria of Escherichia coli effectively in laboratory test [ 52 ].…”
Section: Nanosynthesis Of Representative Polymers Used In Construcmentioning
confidence: 99%
“…Many studies have been conducted on bacterial removal employing different techniques. Lev et al [60] demonstrated an E. coli removal method in wastewater by employing electrospun polyurethane nanofibers. As shown in Table 5, PAN fibers with 10 wt% PVP and 5 wt% gentamicin showed better results, with the total coliform concentration reduced to 980.4 MPN/100ml and the E. coli concentration reduced to 1,119.9 MPN/100 ml.…”
Section: Bacterial Analysis Of Filtered Wastewater Samplesmentioning
confidence: 99%